2013
DOI: 10.1007/s10895-013-1213-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyridine-Based 1,3,4-Oxadiazole Derivative as Fluorescence Turn-On Sensor for High Selectivity of Ag+

Abstract: An oxadiazole derivative(OXD) containing symmetrical pyridine-2-formamidophenyl-binded moiety was synthesised as fluorescence turn-on sensor OA1. Its ultraviolet-visible(UV-vis) and fluorescent spectra(FS) gave prominent fluorescence enhancement only for monovalent silver ion(Ag(+)) in HEPES buffer solution (10 mM, pH = 7.0, DMF-H2O, 9:1, v/v), which indicated the photo-induced electron transfer(PET) occurred from the donor of pyridine-2-formamidophenyl group to oxadiazole fluorophore. The present study demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…However, the catalytic system composed of Pd(dppf)Cl 2 and Bu 4 NBr was the most effective combination, leading to a product yield of 85% (Table 1, entry 6). Additionally, other solvents, such as dioxane, ethanol, 1,2-dimethoxyethane (DME), and dimethylformamide (DMF) ( Table 1, entries [11][12][13][14] were tested, but overall, the best results were achieved using a two-phase toluene-water mixture (Table 1, entry 6). Optimization of the synthetic conditions also required investigating the influence of the type of base used in the reaction, which participates in (i) halogen ion exchange involving the initial halide-containing reagent, 2a, at the surface of the catalyst, and (ii) activation of boronic ester, 6, to facilitate transmetalation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the catalytic system composed of Pd(dppf)Cl 2 and Bu 4 NBr was the most effective combination, leading to a product yield of 85% (Table 1, entry 6). Additionally, other solvents, such as dioxane, ethanol, 1,2-dimethoxyethane (DME), and dimethylformamide (DMF) ( Table 1, entries [11][12][13][14] were tested, but overall, the best results were achieved using a two-phase toluene-water mixture (Table 1, entry 6). Optimization of the synthetic conditions also required investigating the influence of the type of base used in the reaction, which participates in (i) halogen ion exchange involving the initial halide-containing reagent, 2a, at the surface of the catalyst, and (ii) activation of boronic ester, 6, to facilitate transmetalation.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these compounds are well-known and already applied in the medicinal field, as integrase inhibitors to treat HIV (raltegravir) [1,2], hepatitis B and C virus (HBV, HCV) inhibitors [3,4], anticancer drugs (zibotentan), and as antimicrobial (furamizole) [4,5], antifungal [4,6], and antiallergic agents [7]. Because of their favorable thermal and luminescent properties, compounds based on the 1,3,4-oxadiazole ring are also candidates for optoelectronic materials, including organic light emitting diodes (OLEDs) [8,9], liquid crystals [10], metal ion sensors [11,12], and coordination polymers [13]. The most popular method for synthesizing the 1,3,4-oxadiazole scaffold involves cyclization of N,N -diacylhydrazine promoted by SOCl 2 [14], BF 3 •Et 2 O [15], TsCl and various bases including 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU), Et 3 N, pyridine [16].…”
Section: Introductionmentioning
confidence: 99%
“…These ion probes are devised to covalently link fluorophores with a receptor by means of non-conjugating spacer groups and reversibly switch fluorescent intensity ON, after binding the desired ion. Zheng et al reported an interesting example of a PET ion sensor [49], where they employed 1,3,4-oxadiazole as the fluorophore and connected it to two pyridine-2-formamidophenyl ( 28 , Figure 12). The nitrogen atoms of pyridine rings are both the cation receptor and the quenching agent that operate via PET.…”
Section: Metal Ion Sensingmentioning
confidence: 99%
“…Isatoic anhydride (IA, Figure ; chemical name: 2 H -3,1-benzoxazine-2,4­(1 H )-dione; C 8 H 5 NO 3 and CAS registry number: 118-48-9) as an extremely versatile heterocycle has attracted great attention in recent decades because of the ease of its reactions with electrophiles or nucleophiles. , With the ability to undergo various cyclization reactions, IA and its derivatives have been used extensively in the synthesis of agricultural chemicals, pharmaceuticals, pigments, and fragrances. Moreover, it is an important raw material for the production of the selective herbicide bentazon, which is widely used to control broad-leaved and sedge weeds with the advantage of high efficiency, low toxicity, and high activity. Besides, a lot of work has been carried out in exploring the reaction of IA with nitrogen nucleophiles to produce quinazoline and quinazolinone derivatives, which is facilitated by IA’s medicinal properties such as anti-inflammatory and analgesic activity, as well as antimicrobial activity. , Currently, there are three methods to synthesize IA: reaction of anthranilic acid with phosgene or chloroformate, oxidation of isatin, and rearrangement of anthranilic acid derivatives. In actual industrial production, all of the methods would produce a lot of impurities, byproducts, and intermediate products, resulting in the low yield and purity of IA. , Hence, the synthetic products have to be recrystallized to improve the purity through solution crystallization, in which a suitable solvent system would be a determining factor for process performance.…”
Section: Introductionmentioning
confidence: 99%